Case report: Hemangioblastoma in the brainstem of a dog - Landsgaard, Kirsten; St. Jean, Samantha; Lovell, Stephanie; Levine, Jonathan; Gremillion, Christine; Summers, Brian; Rech, Raquel R. (Frontiers in Veterinary Science, 2023)
A 3-year-old, castrated male, American Pit Bull Terrier was presented to Texas A&M University due to a 3-weeks mixed cerebellar and general proprioceptive ataxia, circling, head tilt, and dull mentation. Neurologic examination revealed signs of vestibular and mesencephalic dysfunction. Post mortem examination revealed a 1.1x1x0.8 cm, soft, dark red, well-circumscribed, left sided mass, extending from the crus cerebri of the midbrain caudally to the pons. Microscopically, the neoplasm was composed of a spindle shaped interstitial population of cells interspersed between a prominent capillary network, consistent with the reticular pattern of hemangioblastoma. Interstitial cells had strong, diffuse, intracytoplasmic immunolabelling for neuron-specific enolase (NSE) and were variably positive for intracytoplasmic glial fibrillary acidic protein (GFAP). Vascular endothelial cells had strong diffuse, intracytoplasmic immunolabelling for von Willebrand factor (VWF) glycoprotein. To date, only six cases of hemangioblastoma have been reported in canines, five in the spinal cord and one in the rostral cerebrum. Our case may represent the first canine hemangioblastoma localized to the brainstem.